Proceedings of International Conference on Agriculture 2022
DOI: 10.17501/26827018.2021.6105
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Adoption of Conservation Agriculture Towards Climate Change Adaptation: A Case of Nkomazi, Mpumalanga Province

Abstract: Climate change is a threat to agricultural productivity and the overwhelming effects of climate change hinders the quest for sustainable agriculture, with the aim of satisfying the increasing demands for food and fiber. Adaptation to the ever-changing climate is a necessity for the agricultural sector. The study was conducted in Nkomazi Local Municipality. The study assessed the adoption of conservation agriculture in relation to climate change by smallholder farmers. Focus group discussion, structured and sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Significantly, CA helps to further achieve Sustainable Development Goals 1, 13 and 15, that is Zero Hunger, Climate Action and Life on Land, respectively. Minimal soil disturbance, optimal soil cover and crop diversification are the three main pillars of CA [7,8]. According to [8][9][10][11], CA is a resource-saving farming mechanism.…”
Section: Delineation Of Conservation Agriculturementioning
confidence: 99%
See 3 more Smart Citations
“…Significantly, CA helps to further achieve Sustainable Development Goals 1, 13 and 15, that is Zero Hunger, Climate Action and Life on Land, respectively. Minimal soil disturbance, optimal soil cover and crop diversification are the three main pillars of CA [7,8]. According to [8][9][10][11], CA is a resource-saving farming mechanism.…”
Section: Delineation Of Conservation Agriculturementioning
confidence: 99%
“…Minimal soil disturbance, optimal soil cover and crop diversification are the three main pillars of CA [7,8]. According to [8][9][10][11], CA is a resource-saving farming mechanism. Therefore, forestry cannot be an exception in the use of this beneficial farming system.…”
Section: Delineation Of Conservation Agriculturementioning
confidence: 99%
See 2 more Smart Citations
“…In Mpumalanga province, studies on small-scale farmers' climate change adaptation are few. In literature, few authors reported on climate change perceptions by farmers (Ajala, 2017;Elum et al, 2017;Boluwatife, 2019;Nesamvuni et al, 2022), adaption strategies used by farmers (Ubisi et al, 2020;Sithole and Agholor, 2021). Despite the paucity of research on adaptation perception and adaptation strategies used for climate change, there is no literature on the drivers of climate change in general and modern climate change adaptation methods in Mpumalanga Province.…”
Section: Introductionmentioning
confidence: 99%